Transformasi Limbah Industri Tahu di Dusun Giriharja: Pengelolaan Berbasis IPAL Anaerobik untuk Mendukung Keberlanjutan Lingkungan Perairan - Dinda Mardiani Lubis; Rudiansyah Rudiansyah; Lizha Dwi Mulya Putri (LPPM Universitas Bina Insan, 2024)
This study aims to examine community perceptions of tofu industry waste management in Giriharja Hamlet, Sumedang Regency, as well as the role of anaerobic wastewater treatment plants (WWTP) in supporting environmental sustainability and aquatic resources. Data were collected through observation, interviews, questionnaires, and literature reviews using a qualitative descriptive approach. Respondents consisted of 52 local residents and tofu producers. The findings indicate that prior to the implementation of the anaerobic WWTP, the community faced environmental disturbances, including unpleasant odors from liquid waste. After the WWTP was established, liquid waste was processed into biogas, benefiting 88 households as an alternative to LPG, and its effluent was safely discharged into the environment. Solid tofu waste was also utilized as livestock feed, providing economic value to both the community and tofu producers. The anaerobic WWTP successfully reduced COD levels by over 90%, enhanced environmental quality, and generated renewable energy. Community perceptions of waste shifted from negative to positive, recognizing waste as a valuable new resource. The study underscores that technology-based waste management is crucial for mitigating environmental impacts, supporting the circular economy, and contributing to sustainable development goals, particularly in clean water access, renewable energy, and community welfare.